Analisis Peran Trainee Dalam Meningkatkan Kualitas Pelayanan Concierge di Lorin Solo Hotel - Mardian, Erwin; Darmaesti, Darmaesti; Elizabet Sagala, Afrilia (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to analyze the role of trainees in supporting the quality of concierge services at Lorin Solo Hotel. The research employed a descriptive qualitative method, collecting data through observation, interviews, and literature review, with participants consisting of concierge trainees, bellcaptains, and the trainee coordinator. The findings reveal that trainees play a crucial role in daily concierge operations, such as welcoming guests, assisting with luggage, providing basic information, and supporting light administrative tasks. Their presence helps speed up service delivery, reduce the workload of permanent staff, and strengthen guest interaction, particularly during high season periods. However, several challenges were identified, including limited experience and practical skills, insufficient knowledge of hotel products and local destinations, lack of active supervision, and short internship durations. These factors impact certain service dimensions, such as assurance and reliability. The study recommends comprehensive pre-placement training, the development of specific SOPs for concierge trainees, improvement in foreign language skills, and regular mentoring from senior staff. These measures are expected to enhance trainee professionalism and overall concierge service quality.